Return to play after thigh muscle injury: Utility of serial ultrasound in guiding clinical progression - Hall, M. M. (Current Sports Medicine Reports, 2018)
Return to play after thigh muscle strain injury is difficult to predict and recurrent injury rates are high. There is currently no agreement on the optimal return to play protocol following muscle injury and utility of imaging is debated. Ultrasound has become an increasingly utilized imaging modality and offers several potential advantages for monitoring the return to play process following muscle injury. An ultrasound scanning protocol is presented which provides real-time guidance on muscle healing and may assist with identification of those athletes at risk of reinjury who otherwise appear clinically fit for return to play.